Financial Distress Prediction Analysis at PT Garuda Indonesia Tbk for 2020-2023 Using the Grover, Taffler and Springate Methods - Hasanah, Fayza Safira; Hasanah, Ananda Putri; Budianto, Erwin (Research Collaboration Community (RCC), 2025)
This study aims to evaluate the potential financial distress of PT Garuda Indonesia Tbk during the period 2020-2023 using three prediction models: Grover, Taffler, and Springate. Financial distress is an early sign of financial instability that can lead to bankruptcy, so it is important to analyze it to prevent greater risks. This study uses a quantitative descriptive method with secondary data from the company's financial statements. The results of the analysis show that although Garuda Indonesia's financial condition improved in 2021 and 2022, financial stress returned in 2023. The Grover model is more sensitive in identifying financial distress, while the Taffler method tends to be optimistic, and Springate shows more variable results. Based on these findings, companies need to implement more effective financial strategies to maintain their stability and reduce the risk of bankruptcy.